Stacked LSTM-GRU Model for Traffic Anomalies Detection - Alsyaibani, Omar Muhammad Altoumi; Utami, Ema; Raharjo, Suwanto; Hartanto, Anggit Dwi (Telematika, 2022)
This study aims to improve the accuracy of the intrusion detection system model. It focused on LSTM and GRU methods proposed by several previous studies. The bidirectional layer was also tested to see if it improves model performance. Dataset used in the study was CIC IDS 2017. The dataset was divided into 3 parts, for training, validation, and testing purposes. Validation data was used to evaluate model performance in every training iteration. It helped to make the model would not overfit the training data. Furthermore, Dropout layer and L2 regularization were also added to the model architecture. The training model was done in a binary classification approach with a learning rate of 0.0001. We found that the stacked method reached accuracy 98.1087% in 100 iteration training. This result is slightly higher than LSTM, GRU, Bidirectional LSTM, and Bidirectional GRU. The method which contains LSTM layer performed its best accuracy using Tanh activation. Differently, GRU and Bidirectional GRU performed the best performance with Lrelu and Prelu activation function, respectively. All models could reach the plateau in the first 20 iterations, while in the next 80 iterations the model performance still could be fluctuately improved. Even though the model already reached the plateau in 20 iteration training, it is still possible for the model to slowly improve by using a small learning rate and by implementing Dropout layer and L2 regularization. Fluctuation of model performance implies that the highest model performance was not always reached in the last training iteration. ModelCheckPoint could help to overcome the issue. In addition, the Bidirectional layer increased the complexity of the model which certainly increased training duration. The bidirectional layer improved the performance of the GRU method, but it did not improve the performance LSTM method.